Employment and Economic Potential of State Owned Chir Pine forests in Himachal Pradesh - Suyal, B. D. (Indian Forester, 2017)
The article highlights that despite wide ranging condemnation, the chir pine forests in Himachal Pradesh contribute significantly to the state exchequer and to the rural economy. In brief, the afforestation activities generated 821.64 lakh man days between 1950-51 to 2013-14. The Government owned chir pine forests contribute `486.65 lakh per year to the State as royalty of trees harvested and `654.39 lakh on account of royalty of resin blazes. The annual value of timber traded by the State Forest Development Corporation is `1482.81 lakh and the annual sale value of rosin and turpentine is ` 3578.33 lakh. The value of fuelwood from chirpine forests was estimated to be ` 6952.44 lakh annually. The timber harvesting operations generate 24.52 lakh man days annually for the local people in the State. The extraction of resin also generate on an average about 4.57 lakh man days. Annually about 2538 times, the transport vehicle of 15 cum capacity are put into service to carry the timber to the sale points.